Gathering political writing on art and culture - Pastor-Roces, Marian; Marcelo, Sam L.; De La Salle-College of Saint Benilde (Malate, Manila De La Salle-College of Saint Benilde, Inc. through the Museum of Contemporary Art and Design, 2019)
Marian Pastor Roces is one of the most original thinkers in Southeast Asia addressing the interactions of politics, privilege, state patronage, creativity, tradition, and contemporary art. An art historian, museum director, and cultural theorist, she has shown a keen sensitivity to the relations of power between creators and mediators of art and culture. Gathering is the first-ever collection of essays by Roces, bringing together key pieces in a body of work that is sustained and unrelenting in its commitment to critique in a variety of contexts.
Includes bibliographical references and index.
Keywords: Arts -- Philippines; Art criticism -- Philippines